Pelatihan dan Pendampingan Lesson Study Melalui Model Pembelajaran Project-Based Learning Pada Guru SMP Gucialit - Ana Rokhmawati; Devi Rahayu Agustin; Naily Rizqi Amaliyah (Jurnal Pengabdian Masyarakat Waradin, 2025)
At SMP Negeri 2 Gucialit, teachers have difficulty designing and implementing learning models that can develop students to have skills in critical thinking and problem solving, creative thinking skills, communication skills, and collaboration skills. The aim of this community service is to expand understanding of concepts and improve the skills of Junior High School teachers in designing project-based learning through lesson study. The method used in community service consists of three stages, namely preparation, implementation and evaluation. In the preparation stage, field survey activities and coordination with service partners were carried out. At the implementation stage, material is provided, practice is carried out in developing project-based learning teaching modules through lesson study and discussion. At the evaluation stage, an assessment of the results of the activities was carried out using a questionnaire distributed to participants by the community service team. Based on the results of the questionnaire, it shows that the percentage of answers achieved was 59.3% strongly agree with the benefits of this activity, 37% agree, 3.7% neutral, and there were no answers strongly disagree or disagree. This shows that this service activity increases the understanding of the concepts and skills of Junior High School teachers in designing project-based learning through lesson study. Apart from that, this community service activity produces project-based learning teaching module products and aquascape learning media.